L'habitat gaulois de Feurs (Loire) Fouilles récentes (1978-1981) - Vaginay, Michel (Documents d'archéologie française, 1988)
This work is the result of rescue archaeology carried out at Feurs (Loire) from 1978 to 1981. A series of excavations on the site of the Roman town revealed an earlier Gaulish settlement at its height during the late La Tène period. The discovery of evidence of pre-Roman occupation was completely unexpected since the cantonal capital of the Segusiavi, Forum Segusiavorum, was founded by Augustus and its origins were assumed to date from this period. Based upon the systematic analysis of a large number of finds series, the author's study outlines how the different aspects of the Gaulish settlement of the site developed during the century preceding Caesar's conquest. Seen within the context of inner Gaul, Feurs is of fundamental importance to our understanding of Gaulish civilisation at the end of the Iron Age.